Research in organizational change and development - Shani, Abraham B. (Rami); Noumair, Debra A.; Zandee, Danielle P.; Coghlan, David (Emerald Publishing Limited, 2025)
Volume 31 of Research in Organizational Change and Development addresses emerging issues, challenges and opportunities while advancing new insights to practice and theoretical development. Contributions are devoted to a few timely concerns and emerging organizational challenges. The role that Organizational Development (OD) can play in helping organizations integrate Artificial Intelligence (AI) and Digital Technology - while focusing on issues of design, planned change roadmaps, and collaboration and change methodologies - are explored. Two of the chapters magnify the role that action research methodology plays in the infusion of AI literacy in a business school and in enhancing inter-organizational collaboration in the public health sector. Several chapters address the role that OD can play in the development of new capabilities such as ambidexterity, the moral purpose of the OD profession, and a scholar-practitioner system-based integrated organization development consulting model. One chapter focuses on group dynamics and advancing a sociological perspective that is embedded in a habitus change orientation. The volume concludes with a contribution that builds on the legacy of Ed Schein, where the authors identify trajectories of broad areas for future exploration and development of the field.
Includes index.
Keywords: Organizational behavior.; Business & Economics -- Organizational Behavior.; Business and Management.; Organizational theory and behaviour.; elektronické knihy; electronic books